ENSEÑAR APRENDER LA CIENCIA COMO INVESTIGACIÓN - Ishiyama Cervantes, Raúl (2019)
In the country it was thought that the scientific research it could make only certain people, presently is within reach of all. In the last years terminologies and definitions have been created that "assure" the validity the project and after the results; it caused that courses on investigation were created, each one with its own methodology. The Concytec established the Scholastic Fair of Science and Technology with the purpose of waking up vocations by the investigation from the school. This work was made on base to the scholastic fairs interviewing to students and professors of schools; in addition to professors to courses of investigation in the universities and professionals who graduated with thesis. One was that the students of schools have interest by the investigation, the university students see it more complicated and consider to investigate is difficult by the detailed courses on methodology of the investigation that impose to them, those that graduate with thesis delayed in average a year in culminating it. Teaching to make the investigation in natural form and practice is pleasant for the students.